ARDUINO BASED SMART SOLAR PHOTOVOLTAIC REMOTE MONITORING SYSTEM - V, Vinoth Kumar; Sasikala G, (Malaysian Journal of Science, 2022)
The continuous monitoring system of the photo voltaic solar based energy model is currently highly crucial to monitor the overall performance and other related characteristics of energy solar energy systems from remote locations. For this, data loggers also play a vital role. These technologies are highly important to identify any malfunctions inherent in PV based solar energy systems. The proposed IoT based system is useful to obtain real time data from PV based solar energy systems from remote areas. An Arduino ATMEGA16 microcontroller was used to acquire real time data from the system, which is incorporated with the blynk app to transmit real time data to the destination through a webpage. The proposed system consists of a PV based solar system, Arduino controller board Wi-Fi module and the blynk app, in order obtain and transmit data from any remote location. We have developed a cost effective IoT based Smart monitoring system for PV based solar energy applications to monitor the various characteristics and performance of the system, as well as to carry out preventive maintenance and fault detection.